Communication for Social Change and Socio-Humanistic Training: Theoretical Perspective on Overcoming Racialized Equity Gaps (Islas, 2025)
Introduction: The following article aims to provide a theoretical systematization of the relationship between communication for social change and socio-humanist training. Given its central role in bridging racialized equity gaps, this issue requires new perspectives to achieve greater levels of coherence with the inclusive social orientation that is the essence of the Cuban model of society under construction.Methods: Materialist dialectics was used as the general method, and a qualitative-quantitative research paradigm was adopted. The theoretical method of analysis-synthesis, combined with induction-deduction, allowed us to determine the regularities and trends in the subject. A bibliographic review was prioritized to validate the theories and concepts adopted.Results: Communication and its connection to social inequalities expressed as racialized equity gaps were examined. Emphasis was placed on the qualitative uniqueness of this content for its inclusion in the socio-humanist dimension of training. It was conceived from an innovative perspective that reconfigures and justifies its inclusion in favor of a non-racialized communicative practice.Conclusions: These results provide a philosophical and pedagogical perspective for understanding these relationships: communication and socio-humanist education as a process and outcome in and for social change. This underpins the relevance of particularizing raciality in delimited structuring, as a cause for the harmonization of conflicting racial issues, combined with raising awareness and eradicating inequalities rooted in the popular imagination and sociohistorically communicated cultural symbols.
Keywords: communication; socio-humanist formation; social inequalities; racialized equity gaps